Effects of Steroidal Antiandrogen or 5‐alpha‐reductase Inhibitor on Prostate Tissue Hormone Content. Issue 6 (1st February 2017) - Shibata, Yasuhiro; Arai, Seiji; Miyazawa, Yoshiyuki; Shuto, Takahiro; Nomura, Masashi; Sekine, Yoshitaka; Koike, Hidekazu; Matsui, Hiroshi; Ito, Kazuto; Suzuki, Kazuhiro
Abstract : BACKGROUND: The effects of a steroidal antiandrogen (AA) and 5‐alpha‐reductase inhibitor (5ARI) on prostate tissue hormone content and metabolism are not fully elucidated. The objective of this study is to investigate the hormone content and metabolism of the prostate tissues of patients treated with AA or 5ARI using the ultra‐sensitive liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method. METHODS: Thirty‐nine patients with benign prostatic hyperplasia (BPH) undergoing transurethral surgery were included. Serum and prostate tissue hormone and prostate tissue hormone metabolism analyses were performed using LC‐MS/MS after 1 month of treatment with chlormadinone acetate (CMA; steroidal AA, 50 mg/day) or dutasteride (DUTA; dual 5ARI, 0.5 mg/day). RESULTS: Serum testosterone (T), dihydrotestosterone (DHT), and adrenal androgen levels were lower in the CMA group than the control group. Prostate tissue T and DHT levels were also lower in the CMA group than the control group. In the DUTA group, only serum and prostate DHT concentrations were reduced compared to the control group; in contrast, those of other hormones, especially T and 4‐androstene‐3, 17‐dione in the prostate tissue, showed marked elevations up to 70.4‐ and 11.4‐fold normal levels, respectively. Moreover, the hormone metabolism assay confirmed that the conversion of T to DHT was significantly suppressed while that of T to 4‐androstene‐3, 17‐dione was significantly accelerated in the prostate tissue of DUTA‐treated patients. CONCLUSIONS: Although treatment with AA and 5ARI show similar clinical outcomes, their effect on tissue hormone content and metabolism varied greatly. Prostate 77: 672–680, 2017 . © 2017 Wiley Periodicals, Inc.